Reconstruction of Islamic Religious Education Learning Based on a Multidisciplinary Approach in Facing Digital Transformation and Artificial Intelligence - Andi Wulan Purnama; Muhammad Ivansyah; Faid Kholidi (Konsultan Jurnal Ilmiah Indonesia, 2026)
The digital transformation and development of artificial intelligence (AI) have shifted the paradigm of Islamic Religious Education (PAI) learning and presented challenges in maintaining its relevance to the needs of a digital society. This study aims to analyze the urgency of reconstructing Islamic Religious Education (PAI) learning based on a multidisciplinary approach in addressing digital transformation and the development of AI. The study employed a qualitative approach with library research. Data were obtained from scientific articles, books, proceedings, and relevant national and international institutional documents. Data were analyzed using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that reconstructing Islamic Religious Education (PAI) learning requires integrating Islamic studies, educational technology, psychology, sociology, digital ethics, and data literacy to achieve adaptive, contextual, and character-building learning. The use of AI should be positioned as a learning support instrument, used proportionally under teacher guidance, to strengthen students' critical thinking skills, digital literacy, and moral responsibility. This study provides a conceptual contribution to the development of innovative, humanistic, and Islamic-value-based PAI learning in the digital era.